Contemporary Islamic art of Iraq country: it's appreciation / Fatimatuzzaharah Mohd Kidin - Mohd Kidin, Fatimatuzzaharah (2016)
The contemporary Islamic art of Iraq enhanced in art spirit of Islam especially among asian muslims. It is to understand these works one needs to define the concept of contemporary Islamic alt the aesthetic and culture as well as according to its context. Consideration on the description, analysis, interpretation and judgment in the analysis of the art works is with combine it with the Islamic concept of God and His relationship with His creation. These concept components of analysis on the five artworks will show the reflection of the act of rhythm artist in their remembrance of God. With their own identities shows a unification of the western approached of art with the Iraqi culture. Hence, a reflection of using the established style found in the contemporary art in the west. This is creating and international phenomena in the development of art especially in Iraq.